(untitled) (Bangladesh Medical Journal, 2019)
In Bangladesh, 4 million students study in 64000 madrasha, which represent 7% of all students, most of these are unregistered. There is little evaluation of helminthic infestation by any authority. It is believed that madrasha students came from vulnerable part of society. : Present Sheikh Hasian government declared on equivalency of their certificate therefore it is important to study on them and evaluate their helminthic infestation. May be this is one of the first study on helminthic infestation on grass root level madrasha students in Bangladesh. We conducted the study to evaluate on helminthiasis to find out current situations, to identify the risk factors and for intervention to control of helminthic infestation. This cross sectional study was conducted on 164 from 1000 residential students by simple random sampling. Face to face interview and anthropometric measurement were conducted by semistructured open ended questionnaire from those students. Out of hundred-sixty four students all were male, age range from 06-18 years, ova found 75% students in their stool sample, 71% have multiple helminthasis, Ascaris Lumbricoids (AL) was the most (28%) prevalence, in polyparasitism 58% were Ascaris Lumbricoids and Trichuris Trichuria (AL+TT), anal itching found 68% students which indicate pin worm, no antihelminthic intake 76% students within 6 months. Teachers and parent’s health education help to prevent helminthasis. Regular survey, evaluation is needed to identify the risk factors of helminthasis for intervention, monitoring, guidance and training of students and teachers to improve their personal hygiene practice. Moreover need to intake of regular antihelminthic for dewarming to build a healthy green Bangladesh. Bangladesh Med J. 2019 May; 48 (2): 44-47